Analisis Subsidi Solar Pra dan Pasca Pandemi - Dwika Darinda; Aprilianto Amir (Business Perspective Journal, 2022)
In terms of implementing the government spending especially for subsidy, continuing improvement of implementation is needed to get more effective and efficient. The Government Expenditure is a program that encourages and maintains public consumption, especially those with low incomes. Completion of subsidy spending is important given the limited fiscal space so that it needs to be implemented as well as possible both in terms of optimization and welfare improvement. Therefore, we analyze the diesel subsidy as one of the fuel subsidies that the Government continues to distribute. This study aims to discuss the distribution of diesel subsidies and their impact on poverty and inequality in Indonesia, especially in the pre and post-pandemic period. How does social distancing as a reaction during a pandemic affect the distribution of diesel subsidies. We use the counter factual analysis method as done by Lustig (2018) through part of the Commitment to Equity (CEQ) method. The results of this study indicate that the diesel subsidy program has a positive impact on poverty reduction but is less effective in reducing inequality. This may be due to the lack of accuracy in targeting poverty targets and distributing welfare. Meanwhile, social distancing seems to have little effect on the distribution of diesel fuel due to a decrease in mobility which lowers the economic price. In the future, this research needs to be refined by involving other government social assistance programs to gain insight from these other programs. Keywords: subsidy, Benefit Incidence, Commitment to Equity, Counter Factual Analysis